GESTATIONAL WEIGHT GAIN AND RISK OF AUTISM SPECTRUM DISORDERS IN OFFSPRING : A SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Autism spectrum disorder, more commonly abbreviated as ASD, is a neurodevelopmental condition that can be brought on by a number of different things. Although it is commonly accepted that genetic and environmental factors, as well as the interactions between the two, contribute to autistic phenotypes, the actual causal mechanisms that underpin this phenomena are not yet known to be fully understood by researchers. In this study, the significance of several criteria, including the age of the parents, teratogenic chemicals, prenatal dangers, medication, smoking and alcohol use, food, immunization, hazardous exposures, and the function of severe psychosocial factors, is methodically mapped out. There is a correlation between obesity and systemic inflammation, which can be seen in the increased production of cytokines that happens as a result of an increase in the amount of adipose tissue that has been stored in the body. The United States of America served as the location for the investigation's conduct. Furthermore, GWG that was adjusted for gestational age was associated with ASD, and this association was especially high in male offspring. This finding was consistent across all genders.